ANALISIS DETERMINAN FRAUD DALAM DISTRIBUSI BANTUAN SOSIAL: PERSPEKTIF FRAUD TRIANGLE - Sari, Fangela Myas; Elshifa, Aria; Aria Mulyapradana (Jurnal Bina Akuntansi, 2025)
The purpose of the study was to determine the effect of financial misstatement and the fraud triangle on social assistance fraud. The respondents of the study were 30 employees of the Batang Regency Social Service. Purposive sampling was used in this study. The analysis technique used convergent validity test, reliability test, discriminant test, structural model evaluation, and hypothesis testing with path coefficients. The results of the hypothesis testing analysis showed that the financial misstatement and opportunity variables did not have a significant effect on social assistance fraud at the Pekalongan Regency Social Service. The pressure and rationalization variables had a significant effect on social assistance fraud at the Batang Regency Social Service. Keywords: Financial misrepresentation, Fraud triangle, Social assistance